The Role of Motivation in Mediating the Influence of Organizational Culture, Self-Efficacy, and Fieldwork Practices on College Student Work Readiness (Universitas Negeri Semarang, 2022)
Work readiness is needed to produce qualified workforce candidates who can compete with global demands. This study aims to determine the effect of organizational culture, self-efficacy, and fieldwork practices on job readiness through the motivation of college students in the Accounting Study Program at the Economics College in Semarang City. The research population was all college students in the Accounting Study Program at the School of Economics in Semarang City, totaling 597 college students with a sample of 240 college students taken by proportional random sampling technique. Data collection was carried out using a questionnaire that had been tested for validity and reliability. The data analysis technique used descriptive analysis, path analysis, and the Sobel test. The results show that there is an influence of organizational culture on motivation (22.4%), there is an influence of self-efficacy on motivation (36.9%), there is an influence of fieldwork practice on motivation (24.7%), there is an influence of self-efficacy on work readiness through the motivation of (14,5%), there is an effect of fieldwork practice on job readiness through the motivation of (12,5%), and there is an influence of motivation on work readiness of (36.3%). Meanwhile, organizational culture does not affect work readiness through motivation. This study concludes that motivation successfully mediates self-efficacy and fieldwork practices on college student work readiness. However, motivation did not succeed in mediating organizational culture on the work readiness of college students in the Accounting Study Program at the Economics College in Semarang City.